The Effect of Training Methods and Lemb Muscle Strength on Shooting Accuracy of SSB Satria Perkasa Madiun City (Journal of Physical Education and Sports, 2022)
The purpose of this research is to find out; 1) Analyzing the effect of fixed target training methods and changing target training on the shooting accuracy of the players or athletes of the Satria Perkasa Football School, City of Madiun 2) Analyzing the difference in the effect of high leg muscle strength and low leg muscle strength on the shooting accuracy of Satria Soccer School Mighty City of Madiun. 3) Analyze the effect of the interaction between training methods and leg muscle strength on shooting accuracy at the Satria Perkasa Football School, Madiun City. The research method used was an experimental method with a 2 x 2 factorial design. The population of this study were 24 players or athletes from the Satria Perkasa Football School, Madiun City. The results of the parameter findings in the Anova test study showed that the results of the fixed target training method and changing target training on the shooting accuracy of the players or athletes at the Satria Perkasa Soccer School, Madiun City were (0.039 <0.05), the second parameter finding was the result value the significance of high and low leg muscle strength to the shooting accuracy of Satria Perkasa Football School players or athletes in Madiun City is (0.017 <0.05), then the results of the third parameter finding, namely, the value obtained from the interaction between training methods and high leg muscle strength on the shooting accuracy of the players or athletes of the Satria Perkasa Soccer School in Madiun City is (0.011 <0.05). In conclusion, the fixed target training method is significantly better.